DID MOST BRITS FAIL IN THEIR CIVIC DUTIES IN THE EU REFERENDUM?. Issue 45 (5th January 2017) - Easton, Christina
Abstract : What sorts of reasons should citizens have in mind when they cast votes? Arguments from both sides of the EU referendum debate are used here to raise questions about what our motivations should be when voting. The article introduces John Rawls's requirement to give public reasons that are acceptable to all reasonable people.